ANALISIS BELANJA ONLINE MELALUI SMARTPHONE DENGAN MENGGUNAKAN EXTENDED TECHNOLOGY ACCEPTANCE MODEL - Nining Heriyanti; Muhammad Riza Firdaus; Rusmiyati (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
The purpose of this study is to explore the conceptual model for analyzing customer perceptions of the use of mobile commerce services especially smart phones for online shopping. Results of this study are expected to provide insights into the theory of consumer behavior and the results have practical implications for designers, managers, marketers and developers of mobile shopping site pages. The sample included 155 respondents through online questioner. The use of online questioner is to ensure that respondents who fill the questionnaire are correct respondents who used the Internet access. The next filter is to ensure the respondents truly the one who ever shop online, the design of questioner is made the question in the beginning, whether the respondent ever shop online. If the respondent have not shop online yet, the question jump to the end of the questionnaire. Online shopping experience to further filter to ensure that the respondents were filling has enough experience to shopping online. So the respondents who only had onetime expenditure with online media are not included in the analysis. Data analysis techniques used in this study is using Structural Equation Modeling (SEM) with the help of the program AMOS version 21. Results show that perceived ease of use, perceived usefulness and compatibility has a significant relationship with behavioral intention to use smart phones for online shopping. Behavioral intentions have a significant relationship with actual use. The results are expected to provide theoretical implication to complement existing marketing literature and supports previous studies. The practical implications of this research can be used as the basis for taking measures and appropriate marketing strategies to take advantage of both the perpetrator marketing of new marketing channels, namely smart phones as shopping online media. Originality of this research is specifically discusses online shopping on one device, especially smart phones are still rare.